2018
DOI: 10.4236/scd.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

Review: Umbilical Cord Stem Cells

Abstract: The use of umbilical cord blood as an alternative to bone marrow as a source of haematopoietic stem cells for the treatment of certain diseases has been on an increase since the first transplantation of umbilical cord-derived stem cells in 1988. In this paper, 6 of the latest case studies about the use of such stem cells have been discussed and are used as evidence to confirm the potential use of the umbilical cord as a source of haematopoietic stem cells for transplantation as treatment to various diseases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…Moreover, the ready availability of stem cells for transplantation purposes encourages their application for clinical purposes. For example, Azzopardi and Blundell [20] have reported in their review article on umbilical cord stem cells that these cells can serve as a source of hematopoietic stem cells for transplantation. Jinhui Shen, et al [21] also reported that peritoneal dialysis effluents can serve as a novel source of hematopoietic stem cells.…”
Section: Stem Cell Toxicity and Apoptosismentioning
confidence: 99%
“…Moreover, the ready availability of stem cells for transplantation purposes encourages their application for clinical purposes. For example, Azzopardi and Blundell [20] have reported in their review article on umbilical cord stem cells that these cells can serve as a source of hematopoietic stem cells for transplantation. Jinhui Shen, et al [21] also reported that peritoneal dialysis effluents can serve as a novel source of hematopoietic stem cells.…”
Section: Stem Cell Toxicity and Apoptosismentioning
confidence: 99%
“…Regenerative medicine (RM) is an emerging field focusing on conservative, non-operative treatment for various disorders, including TMJ disorders. RM treatments involve biologics derived from perinatal tissues, including umbilical cord (UC) ( 7 ). UC derivatives, including UC blood and Wharton's jelly, contain various types of stem cells, including MSCs ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The umbilical cord derives from the yolk sac and contains two arteries, one vein, and a gelatinous substance composed of sulfated proteoglycans with collagenous fibers; known as Wharton’s jelly [ 11 ]. The umbilical cord was found to have great proportions of stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…The first successful stem cell transplant was from umbilical cord blood cells on a 6-year-old-boy with Fanconi anemia in 1988 [ 12 ]. Low immunogenicity, low risk of graft versus host disease, and ease of cell collection are major advantages of using cells derived from the umbilical cords [ 11 ]. Umbilical cord tissue mesenchymal stem cell (UCT-MSC) has been used in recent studies to determine their safety and clinical efficacy [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%